PEMBUATAN MEDIA PEMBELAJARAN INOVATIF DARI LIMBAH KAIN PERCA UNTUK MENINGKATKAN PROSES PEMBELAJARAN TEMATIK DI SDN PETOMPON 01 SEMARANG - Nurmawati Nurmawati; Bnti Muflikah; Sri Sumiyati; Yusak Suharno; Maria Yustina Rensi Dartani (Universitas Muhammadiyah Mataram, 2025)
The simple and cheap yet attractive and innovative learning media can be created from various objects around us including waste fabric scraps. Creativity can make useless waste fabric scraps into products that are useful for learning. The purposes of this community service activity (PkM) is to provide training and assistance to teachers of SDN Petompon 01 Semarang in making learning media from waste fabric scraps. This training activity is expected to empower teachers in developing learning media at SDN Petompon 01 Semarang to be more creative in utilizing waste fabric scraps into learning media so that they can support the learning process in the classroom. This activity was attended by 20 participants and this service was delivered using lecture, discussion, demonstration, and direct practice methods. The results that have been achieved in this community service are an increase in participants in understanding the material presented, an increase in participants in making learning media from waste fabric scraps, and participants can implementation waste fabric scraps in the learning process as learning media